Technology acceptance in internet banking: A generational perspective - Santa Bárbara, José Francisco Ferreirinha (2021)
The technology is up for grabs and it is pretty much shaping up as the future of services, communications and so on. Some people, as well as companies, tend to use it and mostly rely on it to perform their daily basis activities. Some don’t. With that being said it is important to acknowledge why are some generations and sectors so perfectly engaged with terms like internet banking, and other generations and sectors are so reluctant to its usage. This study provides a look at what are the main factors contributing to the generation’s Y and Z technology acceptance. And what’s the difference this acceptance can make in service sectors such as the banking sector. Through the UTAUT (Unified Theory of Acceptance and Use of Technology) Model the factors and benefits of technology will be put up to test. Generation Y and Z partake in an online survey that counted with 311 respondents to determine their technology intention and usage. The advantages and limitations of the proposed framework are also discussed.